Coleta, caracterização e avaliação preliminar de acessos de Stylosanthes spp. - Oliveira, Ronaldo Simão de (2015)
The aim of this work was to organize a Forage Germplasm Bank in the State University of Feira de Santana-BA (BGF-UEFS), to carry out a survey of the occurrence of species of Stylosanthes and do pre-breeding studies in a sample of accessions collected in the Semiarid of Bahia from 2008 and 2014. Five collection expeditions in different Semiarid regions of the State was done as an attempt to rescue the maximum genetic variability available. For the pre-breeding work, 25 accessions of Stylosanthes plus a control were utilized. The methods of analysis of variance (ANOVA) and Restricted Maximum Likelihood/Best Linear Unbiased Prediction (REML/BLUP) were used. The genetic parameters were estimated in order to choose the most precise method to select the best individuals for a breeding program. Finally, it was studied the genetic diversity in order to choose the best combinations to develop segregating populations in a breeding program of Stylosanthes. In total, 225 accessions of Stylosanthes spp. were rescued in the state of Bahia, being 61 from de Northeast of the state, 58 from the Mid North, 59 from São Francisco Valley, 24 from the Mid South and 23 from the Far West. The estimates of the genetic parameters showed that the methods (ANOVA and REML/BLUP) presented divergent values. The REML/BLUP estimated the genetic values with better accuracy, increased the efficiency of selection and therefore decreased the cost of a given breeding program that has the objective to increase the mass production in Stylosanthes. In a sample of the analyzed accessions, four species were found (S. scabra, S. humilis, S. viscosa and S. capitata). Genetic variability among the accessions and the clusters of Tocher and UPGMA were basically defined by the botanical species and some of them were superior for mass production (BGF08-16 and BGF06-15) and for forage quality (BGF08- 006 and BGF08-007).